An Exploratory Study of Sevoflurane as an Alternative for Difficult Sedation in Critically Ill Children*. Issue 7 (July 2018) - Mencía, Santiago; Palacios, Alba; García, Miriam; Llorente, Ana M.; Ordóñez, Olga; Toledo, Blanca; López-Herce, Jesús
Abstract : Objectives: To analyze the effectiveness of inhaled sevoflurane in critically ill children with challenging sedation. Design: Prospective case series. Setting: Two PICUs of university hospitals in Spain. Interventions: Prospective observational study and exploratory investigation conducted in two PICUs in Madrid, Spain, over a 6-year period. Children treated with inhaled sevoflurane due to difficult sedation were included. Sevoflurane was administered via the anesthetic conserving device (AnaConDa) connected to a Servo-I ventilator (Maquet, Solna, Sweden). A morphine infusion was added to sevoflurane for analgesia. Demographic and clinical data, oral and IV sedatives, Sedation and Analgesic Clinical scores, and Bispectral Index Score monitoring were registered. Measurements and Main Results: Twenty-three patients with a median age of 6 months old were included. Fifty percentage of the patients had critical heart diseases. Sedative and analgesic drugs used before starting sevoflurane were mainly midazolam (63%) and fentanyl (53%). Six patients (32%) also received muscle relaxants. Sevoflurane was administered for a median of 5 days (interquartile range, 5.5–8.5 d). Median end-tidal sevoflurane concentration was 0.8% (interquartile range, 0.7–0.85%), achieved with an infusion rate of 7.5 mL/hr (5.7–8.6 mL/hr). After 48 hours of treatment, some sedative drugs could be removed in 18 patients (78%). Median Bispectral Index Score value prior to sevoflurane administration was 61 (interquartile range, 49–62), falling to 42 (interquartile range, 41–47; p < 0.05) after 6 hours of treatment. Six patients (26%) presented withdrawal syndrome after sevoflurane suspension, and all of them had received sevoflurane at least for 6 days. The main side effect was moderate hypotension in seven patients (30%). Conclusions: Inhaled sevoflurane appeared to be an effective sedative agent in critically ill children and can be useful in those patients on mechanical ventilation difficult to sedate with conventional drugs. It can be administered easily in the PICU with conventional ventilators using the AnaConDa system. Withdrawal syndrome may occur with prolonged treatment.